Context-aware framework to support situation-awareness for disaster management. (2017) - Aid, Aicha; Rassoul, Idir
When a crisis event occurs, there is a strong need for any involved decision maker to gather in short time frames relevant situational information from different available data sources, to better understand the caused disruptions. Technological devices proliferation and ICT efficiency in timely information sharing did not leave a choice to responders only to adopt them, supporting their operations. This paper proposes a framework that aims to solve challenges brought by this new paradigm of information sharing. Based on service oriented architecture, our framework relies on web service standard for Devices to make pervasive situation-awareness (SA) environment that allows seamless integration of heterogeneous devices. It also provides solutions to filter in real time received information by taking into account the decision maker's context. This context-aware mechanism plays an important role in making the data source intelligent that delivers personalised view of the situation, relevant to decision maker current needs.